2013
DOI: 10.5815/ijmecs.2013.01.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weekly Quizzes on Students’ Final Achievement Score

Abstract: The present study aimed at investigating the effect of weekly quizzes on Iranian high school students' performance on final achievement tests. This effect, which is technically referred to as washback, is defined as the effect of testing on learning and teaching. Most scholars have attempted to provide guidelines in order to achieve positive washback. While some suggest frequent quizzes as a means of positive washback, others oppose the idea. The proponents claim that frequent quizzes stimulate practice and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…A positive impact on student results have been described in some studies [17][18][19]. Poljičanin et al have described in their study an improved student scoring in written, practical and oral examination after introducing frequent quizzing as part Table 3 Comparison between intervention and non-intervention groups (respiratory block) in terms of midterm and final assessment result.…”
Section: Discussionmentioning
confidence: 99%
“…A positive impact on student results have been described in some studies [17][18][19]. Poljičanin et al have described in their study an improved student scoring in written, practical and oral examination after introducing frequent quizzing as part Table 3 Comparison between intervention and non-intervention groups (respiratory block) in terms of midterm and final assessment result.…”
Section: Discussionmentioning
confidence: 99%
“…Gholami and Moghaddam [7] indicated that the weekly quizzes performed better than the group without quizzes. MaDaniel et al [9] reported quizzing as effective technique to assist mastery and retention of the content.…”
Section: Smtsl Interventionmentioning
confidence: 99%
“…Quizzes promote positive impact upon student retention and mastery of material. Gholami and Moghaddam [7] indicated that the group with weekly quizzes performed better than the group without quizzes.…”
Section: Introductionmentioning
confidence: 99%
“…System Usability Questionnaire (PSSUQ) was used for evaluation purpose [37]. The PSSUQ is comprised of 21 items with 7-point Likert-scale (ranging from strongly agree [1] to strongly disagree [7]). The following illustration portrays a sample question: Lewis, J. R. [37] The PSSUQ consists of seven subscales: design / layout (items 1-3); functionality (items 4-6); ease of use (items 7-10); learnability (items 11-13); satisfaction (items 14-16); outcome / future use (items [17][18][19]; and errors / system Reliability (items [20][21].…”
Section: ▪ Home Buttonmentioning
confidence: 99%
“…Quizzes appear to be a useful assessment method that evaluates overall about what has been taught [1]. Quiz items are designed by focusing on both the application and the combination of concepts [2], which are able to promote flexibility in the usage of information.…”
Section: Introductionmentioning
confidence: 99%